Examination of catchment areas for public transport - Landex, Alex; Hansen, Stephen; Andersen, Jonas L. E. (Proceedings from the Annual Transport Conference at Aalborg University, 2006)
The paper presents an approach to examine catchment areas for stops in high quality public transport systems based on the street network in the examined area. This is achieved by implementing the Service Area function from the ArcGIS extension Network Analyst. The approach is compared to a more simple approach using only the Euclidean distance from the examined stop and the paper describes the differences in detail-level of the results. Furthermore, the paper describes how the Service Area approach can be used to examine increments in the catchment areas by adding extra entrances to stations or by making changes in the street network around the station. The paper also discusses the degree of realism in used GIS networks and how it can affect the size of the catchment areas. It is concluded that the Service Area approach improves the detail-level and accuracy in catchment area analyses. These improvements are well suited for examinations of changes in station entrances and/or street network.